15.3k views
1 vote
Marina simplified the expression 4x + 5(–4x – b) – (x – 2) to be –17x – 8.

What was the value of b?
A. –6
B. –2
C. 2
D. 10

2 Answers

1 vote

Answer: C. 2

Step-by-step explanation:

User Sid Barrack
by
4.9k points
2 votes

Answer:

C

Explanation:

Begin by removing the brackets

4x + 5(-4x - b) = -16x - 5b

-(x - 2) = -x + 2

Add the two binomials together to get the third one

4x -20x - 5b - x + 2 = -17x - 8 Combine the like terms on both sides

-17x - 5b +2 = -17x - 8 Add 17x to both sides

-5b + 2 = - 8 Subtract 2 from both sides

-5b +2 -2 =- 8 -2 Combine

-5b = - 10 Divide by -5

b = -10/-5

b = 2

User Adam Robinsson
by
4.5k points